2016
DOI: 10.1093/humrep/dew207
|View full text |Cite
|
Sign up to set email alerts
|

Embryo selection using time-lapse analysis (Early Embryo Viability Assessment) in conjunction with standard morphology: a prospective two-center pilot study

Abstract: ClinicalTrials.gov: NCT01671644.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Based on the results of this review, no negative effect of EmbryoScope compared with conventional incubator is confirmed. Safety of Primo Vision and Eeva have been confirmed by some observational studies published in recent years[3133, 43]. As to the efficiency, economical burden and embryo assessment time comparison among different types of TLI systems, scarce evidence is now available.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the results of this review, no negative effect of EmbryoScope compared with conventional incubator is confirmed. Safety of Primo Vision and Eeva have been confirmed by some observational studies published in recent years[3133, 43]. As to the efficiency, economical burden and embryo assessment time comparison among different types of TLI systems, scarce evidence is now available.…”
Section: Discussionmentioning
confidence: 98%
“…The use of Eeva® in addition with standard morphology assessment has been compared with standard morphology assessment in few randomized clinical trials with different conclusions. On one hand Eeva® seemed to give objective information for helping embryologists with various levels of experience to choose the best embryo to transfer in a double-blinded multi-center study with 54 patients undergoing blastocyst transfer (Diamond et al, 2015), on the other hand, an observational prospective two-center study did not demonstrate any improvement in cycle outcome when using Eeva® (Kieslinger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Automated annotation of embryo morphokinetic parameters could theoretically tackle these 2 issues, leading to improved workflow, high throughput analysis, and lower subjectivity. However, a commercially available automated TLM system based on few early parameters recently failed in confirming its clinical relevance in a prospective trial (Kieslinger et al, 2016), highlighting the need for a robust and multiparametric automated annotation tool. To our knowledge, only one pilot study reported the set-up of a semi-automated script annotating embryo morphokinetic parameters in humans (Mölder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, employment of conical dishes is required during culture employing a commercially available time-lapse system called EmbryoScope™, which may create a unique beneficial surrounding for the embryo in a lowdensity single-embryo culture. Hitherto, validation of the superiority of these technologies regarding culture conditions is pending (78).…”
Section: Latest Trendsmentioning
confidence: 99%